The Electrokinetic Properties and Flotation Behavior of Quartz And Feldspar in the Presence of Polymeric Surfactants (574d0074-57a9-414d-9659-f9ad28b8b802) - Montaser S. EL Salmawy; Eishi Kusaka; Takahide Wakamatsu (International Mineral Processing Congress, 2003)
"The effect of ethoxylation of long chain alcohols on the quartz and feldspar flotation behaviors was investigated for surfactants of the octylphenol polyoxyethylene family. The tests were carried out with an average of 7.5 (Triton X 114), 9.5 (Triton X 100), 30 (Triton X305), 40 (Triton X 405) and 70 (TritonX 705) oxyethylene units. Electrokinetic and flotation studies on quartz have shown that at low pH values, quartz could be floated with polyoxyethylene octytlphenols. The possible mode of adsorption of these nonionic surfactants may be suggested to be due to hydrogen bonding between the oxygen of ether and hydrogen in the free hydroxyl groups on quartz surface. It was anticipated that the selectivity between quartz and microcline would decrease as oxyethylenic chain length increases.Electrokinetic methods were used to elucidate the mechanism of surfactants adsorption and to correlate these findings with the optimum flotation conditions. The polymeric surfactants would reduce the negative values of zeta potential of quartz while the reverse is true for feldspar. After treatment of microcline with HCl, its electrokinetic behavior in the presence of Tritons X surfactants became similar to that of quartz.The obtained results would suggest that separation of quartz from feldspar using nonionic surfactants of octylphenoletoxylated alcohols having shorter oxyethylenic chain length at low pH could be achieved"